An exploratory evaluation of a paired maths intervention with secondary aged pupils - Cooper, S.J. (2016)
This study presents an exploratory evaluation of a seven week cross-age peer-tutoring mathematics intervention, Paired Maths (based on Topping, Kearney, McGee and Pugh, 2004), as delivered in a UK secondary school. The impact of Paired Maths on the mathematics attainment of tutees, and the self-esteem of both tutees and tutors is evaluated. Paired Maths involves pairs of students, one student in the role of a tutor and one in the role of a tutee, completing mathematics activities together. Tutors are trained to follow a structured process to scaffold their tutee's learning during the activities. Although existing theory and literature suggests that a cross-age, peer-tutoring intervention around mathematics could have a positive impact, no research has experimentally evaluated Paired Maths in the UK secondary school to date. A total of 78 participants, aged 12-15 years, from three secondary schools situated in a small city in England took part. A Randomised Control Trial was used to consider the impact for Year 8 participants in the role of the Tutee. This compared children randomly assigned to either a Paired Maths (Experimental) Group, a Teaching Assistant Led Comparison Group or a Waitlist Control Group. Results showed no statistically significant differences between groups in mathematics attainment or self-esteem. Within the same exploratory evaluation, a Randomised Control Trial was also employed to consider the impact for the Year 10 students in the role of the tutor. This compared children randomly assigned to either the Paired Maths (Experimental) group or a Waitlist Control Group. Although Waitlist Control participants saw a statistically significant decrease on measures of Maths self-concept over time, results showed no other statistically significant differences between groups in self-esteem. Overall, Paired Maths was not considered to have had a positive impact on mathematics attainment for children in the role of the tutee, or on the self-esteem of children either in the role of tutee or tutor. These findings are considered in relation to the literature and methodology adopted, with a number of possible explanations presented. Possible avenues for future research are proposed (within and also beyond the post-positivist paradigm) with the key conclusion that further exploration is needed around what may support the successful implementation of a Paired Maths programme with secondary aged Pupils. Key limitations of the research relate to the measurement of the dependent variables and treatment fidelity.